Too early to market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The high prices for vanilla on the world market (see Spore 98) has been leading to local buyers in Uganda a relatively small producer encouraging farmers to harvest and sell their beans prematurely. Other farmers are harvesting unripe beans to...